Entrepreneurship : Techno Software / Mohd Nazrool Adenan ... [et al.] - Adenan, Mohd Nazrool; Ahmad, Amran; Zakaria, Hazimi; Salimin, Ahmad Shyain (2002)
TECHNO Software Sdn. Bhd is situated at No. 108 Kuala Ibai, KM 8 Jalan Sultan Mahmud, 20400 Kuala Terengganu, Terengganu Darul Iman. We have 29 workers including driver. All workers divided to every sector followed by his job.